Production of omega-3 fatty acids by enzymatic hydrolysis from lemuru fish by-products - Kosasih, Wawan; Tina Rosmalina, R.; Risdian, Chandra; Saepudin, Endang; Sri Priatni, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Production of omega-3 fatty acids from lemuru fish by-products was studied by enzymatic hydrolysis using a lipase enzyme in one liter of the batch reactor. The hydrolysis temperature of fish oil was set at 45 to 55 ℃ for 0 to 24 h, whereas agitation from 50 to 150 rpm. RSM-Box Bhenken was used to study the effect of these parameters on omega-3 (EPA, docosahexaenoic acid (DHA), and α-linolenic acid (ALA)) content. The % free fatty acid (FFA), acid index, peroxide index, iodine index, and saponification index of lemuru fish oil was 0.925, 2.52, 42.5, 97.28, and 160.11%, respectively. GC-MS analysis results showed that unsaturated fatty acids content (62.34%), which are consisted of omega-3 (EPA, DHA, and ALA), omega-6 and omega-9, was much higher than saturated acids (12.97%). The experiment data showed that the highest EPA (1.221%) and DHA (0.312%) content were reached at 50 ℃ and 24 h with 150 rpm of agitation. However, through the RSM-Box Bhenken analysis and 3D surface plot, it was suggested that the optimum condition was obtained at 45 ℃ and 24 h with 150 rpm of agitation with the content of EPA, DHA, and ALA were 1.709, 0.49, and 1.237%, respectively.